Analysis of the educational-communicative language of Spanish archaeological museums during the 2020 confinement - Navarro Neri, Iñaki; Aso Morán, Borja; Mendióroz Lacambra, Ana María (Clio. History and History Teaching, 2021)
The forced physical closure of Spanish museums and archaeological sites during the early stages of the health crisis between March and June 2020 obliged the institutions to focus their informative and educational activity on social networks such as Facebook, Twitter and Instagram. This research aims to analyse whether these archaeological sites use an educational-communicative language in accordance with the social platform they are on, based on the analysis of their online communicative production on Twitter during the first hundred days of the crisis caused by Covid-19 (from March to June 2020).The results show how the Spanish museum institutions in the field of archaeology that were most active on Twitter -even before the pandemic- not only demonstrated that they had perfectly assimilated the educommunicative language, but also chose to expand and diversify their content during the health crisis and the forced closure of physical activity. Likewise, institutions that had previously been less active on this platform developed planned educommunicative activity that was attractive to all audiences.
Keywords: archaeological museums; social media; communication strategies; dissemination of knowledge; Spain